2007
DOI: 10.1002/ppul.20686
|View full text |Cite
|
Sign up to set email alerts
|

The combination of PCR and serology increases the diagnosis of Pseudomonas aeruginosa colonization/infection in cystic fibrosis

Abstract: PCR identified a higher number of patients with P. aeruginosa than serology and conventional culture, but the difference did not reach statistical significance. Any of the combination methods that included PCR resulted in significantly statistical differences in relation to isolated microbiological or serology methods, but not to the PCR method alone, suggesting that PCR may be the main additive method for P. aeruginosa identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
1
44
0
3
Order By: Relevance
“…The use of such techniques would probably have changed the result of the study because the use of PCR and serology in combination has been shown to be superior to the use of each method in isolation, to the combined use of PCR and culture, and to the combined use of culture and serology. (14) The nebulizers used by the CF patients analyzed in the present study presented with a low rate of bacterial growth, although most of the patients did not often use disinfection procedures. There were no associations between the types of bacteria found in the sputum/ oropharynx of patients and those found in the nebulizer parts (mask, mouthpiece, and chamber).…”
Section: Discussionmentioning
confidence: 76%
“…The use of such techniques would probably have changed the result of the study because the use of PCR and serology in combination has been shown to be superior to the use of each method in isolation, to the combined use of PCR and culture, and to the combined use of culture and serology. (14) The nebulizers used by the CF patients analyzed in the present study presented with a low rate of bacterial growth, although most of the patients did not often use disinfection procedures. There were no associations between the types of bacteria found in the sputum/ oropharynx of patients and those found in the nebulizer parts (mask, mouthpiece, and chamber).…”
Section: Discussionmentioning
confidence: 76%
“…A further study using a combination of PCR and Serology showed that it was possible to isolate P. aeruginosa by culture in samples from 42 patients (48.2%), while PCR was positive in 53 (60.9%) [14]. Our results show that in cough swabs P. aeruginosa was positive by culture in 5% samples (11% patients) , while PCR was positive in 11% samples (16% patients) and in sputa P. aeruginosa was positive by culture in 52% of samples (44% patients), while PCR was positive in 76% samples (76% patients).…”
Section: Discussionmentioning
confidence: 92%
“…Most of the studies, comparing the sensitivity of culture and PCR for the detection of P. aeruginosa, are cross-sectional [11,12,[16][17][18][19][20][21]. In all of these studies, an equal or increased detection rate was found with PCR in comparison with culture (Table 2).…”
Section: Sensitivity Of the Qpcr Formatsmentioning
confidence: 94%